Glycaemic control in relation to xanthine oxidase and antioxidant indices in Malaysian Type 2 diabetes patients - Kuppusamy, U.R.; Indran, M.; Rokiah, P. (2005)
Aims Increased oxidative stress and oxidative damage are present in Type 2 diabetes mellitus (DM). The aim of this study was to assess the oxidative stress levels in the three major ethnic groups in Malaysia and to study the association between glycaemic control and oxidant-antioxidant levels in these patients. Methods Oxidative indices and glycaemic control were assessed in 650 Type 2 DM patients and 280 healthy age-matched controls by known established methods. Results Type 2 DM patients had significantly lower levels of antioxidant enzymes and non-enzymatic antioxidant (FRAP) and increased levels of HbA(1c), fasting blood glucose (FBG), malondialdehyde (MDA) and xanthine oxidase (XO) when compared with control: subjects. Markers of oxidative stress were more apparent in Indian patients compared with Malay and Chinese patients. Correlation analysis of oxidant-antioxidant parameters as a function of HbA(1c) in each ethnic group revealed a strong association of HbA(1c) with oxidative indices. Conclusions The present study provides evidence for the possible contribution of XO to oxidative stress and the pathophysiology of diabetes. HbA(1c) remains an important marker of glycaemic control for the management of Type 2 DM, but other confounding factors that predispose or lead to oxidative stress should also be taken into consideration.